South Africa after 30 years of democracy: Land claims and transitional justice in the spotlight - Pulane Adelaide Molomo; Bekithemba Dube (Interdisciplinary Journal of Sociality Studies)
Transitional justice is a universal strategy employed worldwide to secure peace and avoid warfare when an authoritarian regime is succeeded by democratic rule. The short duration of the transitional process and the lesser priority placed on social justice have impacted rural poverty, unresolved land reforms, ideological differences, and inequalities. This literature review explores the disadvantages of transitional justice and government policies regarding land reforms. It traces the causes of conflicts surrounding land that have affected rural poverty by examining the roles played by transitional justice, land acts, and government policies over the past 30 years. The research is underpinned by the conflict theory of Karl Marx and Engels, which does not commit to socialism or capitalism while highlighting the conflict between the wealthy and the poor. The literature reveals that South Africa is experiencing conflicts rooted in socio-economic challenges, political differences, inequalities, and poverty due to unresolved land issues. Based on the findings, the paper concludes that transitional justice has adopted a neo-liberal angle that compromises the rights of Black individuals. The implication is that transformative justice is needed to represent the voices of the people, address inequalities, and enable access to land as a necessity for food security and residential purposes.